Ursus maritimus Phipps 1774 ... - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Ursus maritimus Phipps 1774 Ursus maritimus Phipps 1774, Voyage Towards North Pole: 185. Type Locality: "on the main land of Spitsbergen" [Norway]. Vernacular Names: Polar Bear. Synonyms: Ursus eogroenlandicus (Knottnerus-Meyer 1908); Ursus groenlandicus (Birula 1932); Ursus jenaensis (Knottnerus-Mayer 1908); Ursus labradorensis (Knottnerus-Meyer 1908); Ursus marinus Pallas 1776; Ursus polaris Shaw 1792. Distribution: Canada, Greenland, USA (Alaska), Russia. Circumpolar in the Arctic, S limits determined by ice pack. Conservation: CITES – Appendix II; IUCN – Lower Risk (cd). Discussion: Revised by Wilson (1976). Reviewed by DeMaster and Stirling (1981). Placed in subgenus Thalarctos by Gromov and Baranova (1981). U. maritimus is considered the sister species to arctos (Goldman et al., 1989; Shields and Kocher, 1991). Synonyms allocated according to Ellerman and Morrison-Scott (1951) and Hall (1981). ... : Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 589, DOI: 10.5281/zenodo.7316519 ...